2000
DOI: 10.1161/01.cir.101.18.2172
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Contrast Media Utilization in High-Risk PTCA

Abstract: In this contemporary prospective multicenter trial of PTCA in the setting of acute coronary syndromes, there was a low incidence of in-hospital clinical events for both treatment groups. The cohort receiving the nonionic dimer iodixanol experienced a 45% reduction in in-hospital MACE when compared with the cohort receiving ioxaglate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 21 publications
5
76
0
4
Order By: Relevance
“…The other two contrast media, ioxilan and iomeprol, caused less P-selectin expression, suggesting that common mechanism(s) may be contributing to the differences in both platelet aggregation and degranulation. These results are consistent with the recent results of the COURT trial (contrast media utilization in high risk PTCA, 18) which suggested that isomolar nonionic dimer iodixanol reduced in-hospital major clinical events. Taken together, these data indicate that nonionic molecules directly affect the platelets, implying that any contrast In previous studies the blood samples were collected through a syringe needle, which may have affected the measurement of platelet aggregation.…”
Section: Discussionsupporting
confidence: 92%
“…The other two contrast media, ioxilan and iomeprol, caused less P-selectin expression, suggesting that common mechanism(s) may be contributing to the differences in both platelet aggregation and degranulation. These results are consistent with the recent results of the COURT trial (contrast media utilization in high risk PTCA, 18) which suggested that isomolar nonionic dimer iodixanol reduced in-hospital major clinical events. Taken together, these data indicate that nonionic molecules directly affect the platelets, implying that any contrast In previous studies the blood samples were collected through a syringe needle, which may have affected the measurement of platelet aggregation.…”
Section: Discussionsupporting
confidence: 92%
“…Because patients with CKD reveal a higher frequency of diffuse disease and an increased rate of multivessel disease, applied contrast volumes are generally higher compared with regular patients. 9 Although the incidence of contrast media-induced nephropathy (CIN) in patients with preserved renal function is very low, 10 the risk for patients with risk factors such as chronic renal failure and diabetes is considerably increased and ranges between approximately 12% and 50%. 11 Importantly, it is elevated even in patients with moderate renal dysfunction.…”
Section: Clinical Perspective On P 437mentioning
confidence: 99%
“…The average contrast volume delivered for diagnostic angiography immediately following coronary intervention was 367 mL, which is in good accordance with the COURT trial that studied the impact of different contrast media on the incidence of major adverse cardiac events after PCI. 9 Other trials that included a significant portion of patients solely undergoing coronary angiography without PCI reported the use of lower amounts of contrast media, such as in NEPHRIC 11 (Ϸ163 mL), RECOVER 22 (Ϸ200 mL), and CARE 23 (Ϸ135 mL).…”
Section: Wessely Et Al Contrast Media-induced Nephrotoxicity and Pcimentioning
confidence: 99%
See 1 more Smart Citation
“…19 These changes occur because of cytotoxity and increased viscosity of the contrast media. In the present study, almost all patients had Iodixanol (visipaque), a nonionic, dimeric, and iso-osmolar contrast medium, which is shown to have a low nephrotoxic effect in different subsets of patients with or without impaired renal function, 20,21 but the matter of which type of contrast media that is most kidney-friendly is still under debate. 22 The relationship between impaired renal function after contrast media and prognosis has been well documented with a poorer prognosis for an impaired kidney function, as well in patients with precontrast-impaired kidney function.…”
Section: Discussionmentioning
confidence: 65%